Evans Syndrome- An Unresolved Tale - Divya Sharma; Zubin Pradeep Sharma; Ravindra Sharma; Divya Saraswat (Journal of Medical Biomedical and Applied Sciences, 2020)
Evans syndrome is a uncommon hematologic autoimmune disease characterized by autoimmune hemolytic anemia and immune thrombocytopenic purpura with a positive antihuman globulin test. We report a rare case of Evans Syndrome of a 40 years old female who presented with bleeding per vaginal since 4 days with anemia and thrombocytopenia. The purpose of this case report is to increase the level of awareness among clinicians to instigate an appropriate diagnostic workup in patients presenting with anemia in the setting of ITP. Evans syndrome (ES) is a hematologic disorder characterized by the sequential or simultaneous development of DAT positive autoimmune hemolytic anemia (AIHA), immune thrombocytopenia (ITP) and/or immune neutropenia in the absence of a known etiology.1 Evan’s syndrome is a rare disorder because it is diagnosed in only 0.8% to 3.7% of all patients with either ITP or AIHA at onset.1 Defined by Robert Evans in 1951 when he studied the relationship between autoimmune hemolytic anemia (AIHA) and immune thrombocytopenic purpura (ITP)2.